Prevalence of rheumatoid arthritis among hospital workers in the north of Jordan: Preliminary report of a hospital-based cohort study - Alawneh, Khaldoon M. (Ann Med Surg (Lond), 2020)
BACKGROUND: Rheumatoid arthritis (RA) is the most common autoimmune inflammatory arthritis in adults. Prevalence estimates of rheumatoid arthritis vary in the world. Occupational factors and geographical location might contribute to a higher risk of developing the disease, however the exact etiology remains unknown. The aim of our study was to estimate the prevalence of RA among hospital workers in the North of Jordan and to compare this prevalence with that in the general population. In addition to describing the characteristics of RA patients. METHODS: The study was performed in two stages; during the first stage a specially designed questionnaire was conducted by trained residents with 2569 hospital workers from 6 government hospitals to identify individuals with RA. Suspected individuals of having RA identified in stage one were invited and examined further by two rheumatologists for confirmation of the diagnosis. RESULTS: A total of 2569 employees were interviewed; among them 1240 (48.5%) were males and 1318 (51.5%) were females. The mean (SD) age was 34±(8.4) years. In the second stage the diagnosis of RA according to ACR criteria 1987 was confirmed in 8 individuals (2 males and 6 females). Male: Female (M: F) ratio was 1:3 with mean (SD) age 43.38 (7.52) years. The estimated prevalence of RA among hospital workers in the North of Jordan was 8/2569 = 0.00311, 31.1:10.000, 0.31%, (95% confidence interval, 9.6–52.7:10.000). CONCLUSION: The prevalence of RA among hospital workers in the North of Jordan is 0.31%, similar to that of other parts of Jordan and neighboring regions.